The Effect of Frames on COVID-19 Vaccine Resistance - Palm, Risa; Bolsen, Toby; Kingsland, Justin T. (Frontiers in Political Science, 2021)
In order to control the spread of infectious diseases such as COVID-19, it will be important to develop a communication strategy to counteract “vaccine resistance”, that is, the refusal to take the COVID-19 vaccine even when available. This paper reports the results of a survey experiment testing the impacts of several types of message content: the safety and efficacy of the vaccine itself, the likelihood that others will take the vaccine, and the possible role of politics in driving resistance to the vaccine. In an original survey of 1,123 American M-Turk respondents conducted in the summer of 2020, we provided six different information conditions suggesting the safety and efficacy of the vaccine, the lack of safety/efficacy of the vaccine, the suggestion that most others would take the vaccine, the suggestion that most others would not take the vaccine, the suggestion that the vaccine is being promoted by liberals to gain greater control over individual freedom, and the suggestion that its approval is being by President Trump rushed for political motivations. We compared the responses for those in the treatment groups with a control group who received no additional information. In comparison to the control group, those who received information about the safety/efficacy of the vaccine were more likely to report that they would take the vaccine, those who received information that others were reluctant to take the vaccine were more likely to report that they themselves would not take it, and those who received information about political influences on vaccine development expressed resistance to taking it. Communication of effective messages about the vaccine will be essential for public health agencies that seek to promote vaccine uptake.